Movement of Water Across Passages Connecting Philippine Inland Sea Basins - Meñez, Lambert Anthony B; Villanoy, Cesar L; David, Laura T (Science Diliman: A Journal of Pure and Applied Sciences; Vol 18 No 2 (2006), 2007)
Advection of Pacific water to the inland seas is through a number of straits bordering the archipelago. Movement of water was demonstrated by temperature-salinity diagrams plotted for a number of stations situated along the various passages. As water from the Pacific flowed through the straits its characteristic T-S profile was modified as it mixed with waters of different properties. This was best seen along the San Bernardino-Verde Island transect where strong surface flow during the NE monsoon resulted in separation of profiles at the surface indicating dilution as water moved away from the source. For deeper water, the erosion of the subsurface salinity minimum and maximum representing the core of the intermediate waters showed transport. These waters were restricted by shallow sill along the eastern coast of the country and limited to a depth of 441m by the sill across the Mindoro Strait.